2002
DOI: 10.2214/ajr.179.1.1790149
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Benefit of Maximum-Intensity-Projection Images on Observer Detection of Small Pulmonary Nodules Revealed by Multidetector CT

Abstract: MIP processing reduces the number of overlooked small nodules, particularly in the central lung. Observer nodule detection remains imperfect even when lesions are clearly depicted on images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 23 publications
(51 reference statements)
4
65
0
7
Order By: Relevance
“…However, this phenomenon was not observed in our study since only one and three cancers were missed at consensus double reading and single reading, respectively. This can be explained by the fact that multidetector CT performed at low-dose level provides high spatial resolution and attenuation and the use of maximum intensity projections reconstruction algorithms with cine mode further facilitates the identifi cation of abnormalities ( 22 ). Second, our nodule management strategy is an objective, software-driven approach ( 23,25 ), in which the recall is determined only by the volume and the VDT of the nodules detected without further subjective interpretation.…”
Section: Thoracic Imaging: Consensus Double Reading In Ct Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, this phenomenon was not observed in our study since only one and three cancers were missed at consensus double reading and single reading, respectively. This can be explained by the fact that multidetector CT performed at low-dose level provides high spatial resolution and attenuation and the use of maximum intensity projections reconstruction algorithms with cine mode further facilitates the identifi cation of abnormalities ( 22 ). Second, our nodule management strategy is an objective, software-driven approach ( 23,25 ), in which the recall is determined only by the volume and the VDT of the nodules detected without further subjective interpretation.…”
Section: Thoracic Imaging: Consensus Double Reading In Ct Lung Cancermentioning
confidence: 99%
“…This observation is in line with previous studies. Gruden et al ( 22 ) explored the interreader variability in a lung cancer CT screening project and showed that the difference between readers could have occurred in lesion detection, characterization of a lesion as a nodule or nonnodule, or lesion measurement. The interobserver agreement was moderate to substantial, and potential for considerable improvement existed.…”
Section: Thoracic Imaging: Consensus Double Reading In Ct Lung Cancermentioning
confidence: 99%
“…Investigators developing automated lung nodule detection methods, for example, require the opinion of an experienced radiologist regarding the location of nodules within the CT scans. More appropriately, a panel of experienced thoracic radiologists would be used to establish the "truth" for the nodule-detection task, since radiologists can miss lung nodules (8,9) and the variability among radiologists in the detection of lung nodules is known to be substantial (10-13) (some investigators even incorporate the output from the CAD system itself into the "truth" assessment (14,15)). Furthermore, the notion of a single "truth" in any particular instance is elusive (16), with differences of opinion in the interpretation of images among even experienced thoracic radiologists a reality (13).…”
Section: Introductionmentioning
confidence: 99%
“…8 A study comparing the use of MIP with volume rendering (VR) image processing techniques found VR to be superior to MIP in detecting small pulmonary nodules. 9 These image processing techniques have been further developed using machine learning methods to facilitate computer-aided detection of pulmonary nodules.…”
Section: Improved Data Analysismentioning
confidence: 99%